Studi Islam dan Pendidikan Berbasis Al-Quran - Renanda Khairunnisa; Rizki Amaliyah Kurniadi; Siti Nurhalizah (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Education is one of the joints in religion. Islamic teachings can survive until now, one of which is because there is an educational process in addition to da'wah of course. The preachers who spread to all corners of the world used the Qur'an as a guide both in terms of orientation, purpose, way or method of delivery, media and tools even the material contained in its delivery was taken from the Qur'an. The Qur'an which is all the source of guidance, makes it a very thick inspiration in every movement of thought of Muslims. In many areas of religious Muslim society will always refer to revelation as the word of God delivered through His Prophet. In this case, of course, one of the important elements in it is education.